2011
DOI: 10.4236/jasmi.2011.11001
|View full text |Cite
|
Sign up to set email alerts
|

Application of in-house method for determinationof radium isotopes in environmental samples usingthe Liquid Scintillation counting technique

Abstract: A method for determination of 226 Ra and 228 Ra in environmental samples using the α-β coincidence liquid scintillation counting (LSC) has been developed. Radium were preconcentrated from environmental samples by coprecipitation with BaSO 4 , then purified from others radionuclide interferences using the cation column exchange (Bio-Rad AG 50 W-X4 resin with 200 -400 mesh size and H + form) and operating in warm temperature which is between 70˚C -80˚C. Then, the Ba(Ra)SO 4 precipitate was filtered through the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…In all of these cases, the results are very much lower than that of present observations. Conversely, Ariffin et al 2011 [ 48 ] have reported average activity ranges for 226 Ra and 228 Ra in the soft tissue of fish collected from Kapar, Klang, Malaysia (near to Port Klang and very near to the 2420 MW Kapar coal-fired power plant) of 11.82 ± 5.23 to 16.53 ± 6.53 Bq kg −1 and 43.52 ± 16.34 to 53.57 ± 19.86 Bq kg −1 respectively, being considerably greater than the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In all of these cases, the results are very much lower than that of present observations. Conversely, Ariffin et al 2011 [ 48 ] have reported average activity ranges for 226 Ra and 228 Ra in the soft tissue of fish collected from Kapar, Klang, Malaysia (near to Port Klang and very near to the 2420 MW Kapar coal-fired power plant) of 11.82 ± 5.23 to 16.53 ± 6.53 Bq kg −1 and 43.52 ± 16.34 to 53.57 ± 19.86 Bq kg −1 respectively, being considerably greater than the present study.…”
Section: Resultsmentioning
confidence: 99%